Spatially heterogeneous relief changes, soil formation and floodplain aggradation under human impact: geomorphological results from the Upper Rhine Graben (SW Germany) - Holzhauer, Ingmar; Kadereit, Annette; Schukraft, Gerd; Kromer, Bernd; Bubenzer, Olaf (Zeitschrift für Geomorphologie, 2017)
Holocene landscape evolution under human impact in the middle part of the Upper Rhine Graben area in southwestern Germany has not been investigated systematically. This is all the more surprising, as from the neighbouring loess covered Kraichgau area, human impact on the landscape and corresponding landscape changes have been documented since prehistoric times. The study at hand focuses on a ca. 500 km 2 large segment of the middle part of the URG, east of the river Rhine between Heidelberg, Mannheim and Karlsruhe. This is where the last glacial lower terrace of the river Rhine forms the (near-)surface substratum. The study area participates in different landscape units ("naturräumliche Einheiten"), such as the forested Schwetzinger Hardt area on well drained sites, next to a system of depres- sions with moister conditions. Geomorphic units within these landscape units include inland dunes, cover-sand areas and the alluvial plains of the Kraichbach and Leimbach streams. The prominent elongated depressions in the eastern part of the study area are the remains of an abandoned Lateglacial to Early Holocene fluvial system, the Kinzig-Murg-channel system ("Kinzig-Murg-Rinne"). This paper presents the general stratigraphy of the Holocene sediments and soils of the different landscape and geomorphic units. This is achieved at representative sites along selected transects at the transition zones of these units, which offer the opportunity to reconstruct past geomorphic dynamics and resulting landscape changes. Field investigations are based on Electrical Resistivity Tomography, percussion drillings and soil-sediment profiles of excavated pits, accomplished by sedimentological and mineralogical laboratory analyses of selected samples. Our study shows that part of the Kinzig-Murg-channel system was abandoned by the Bronze Age. Investigations on a smaller scale suggest strong landscape changes in Holocene times, most likely under human impact, as observed in spatially highly variable patterns of soil erosion and sediment accumulation in the dune and cover-sand areas. These observations are supported by few 14C ages which point to strong geomorphodynamics in Medieval times, also in the alluvial plains, likely due to the concurrence of the Medieval inland colonization and the high magnitude of rainfall-runoff events. Accordingly, significant Holocene landscape changes occurred within the last ca. 800 years. These findings of a recently remoulded last glacial landscape are in agreement with findings from the neighbouring old settled Kraichgau area. Moreover, past erosion of Luvisols in the Kraichgau area was recorded and archived in corresponding fine-grained overbank deposits of the Kraichbach and Leimbach streams, pointing to the connectivity between the slopes and the receiving streams, as well as to the geomorphic interrelation between the Kraichgau and the middle URG areas that was established in Medieval times. The applied method, which focusses on the transition zones between geomorphic units, appears applicable for reconstructing the evolution of other landscapes structured on a comparably small scale, as well as for different time periods.
Gesehen am 06.07.2017
Keywords: Kinzig-Murg-Rinne; Oberrheinisches Tiefland